Chlamydia pneumoniae in Alzheimer's disease pathology - Subedi, Lalita; Gaire, Bhakta Prasad; Koronyo, Yosef; Koronyo-Hamaoui, Maya; Crother, Timothy R. (Frontiers in Neuroscience, 2024)
While recent advances in diagnostics and therapeutics offer promising new approaches for Alzheimer’s Disease (AD) diagnosis and treatment, there is still an unmet need for an effective remedy, suggesting new avenues of research are required. Besides many plausible etiologies for AD pathogenesis, mounting evidence supports a possible role for microbial infections. Various microbes have been identified in the postmortem brain tissues of human AD patients. Among bacterial pathogens in AD, Chlamydia pneumoniae (Cp) has been well characterized in human AD brains and is a leading candidate for an infectious involvement. However, no definitive studies have been performed proving or disproving Cp’s role as a causative or accelerating agent in AD pathology and cognitive decline. In this review, we discuss recent updates for the role of Cp in human AD brains as well as experimental models of AD. Furthermore, based on the current literature, we have compiled a list of potential mechanistic pathways which may connect Cp with AD pathology.